Attenuation of the Vibration in a Non-ideal Excited Flexible Electromechanical System Using a Shape Memory Alloy Actuator - Kossoski, Adriano [UNESP] (2021)
This paper presents the implementation of a Shape Memory Alloy (SMA) actuator in a so-called non-ideal system with the objective of reducing the mechanical vibrations and the Sommerfeld effect present in this kind of system. Although SMA materials have been studied for a while, this article contributes by showing experimental results for both the actuator and for its implementation in a vibration attenuation system seeking to evaluate its viability in vibrating systems with more aggressive characteristics. Initially, the SMA actuator was studied separately, where its performance characteristics like actuation force, extension and return were analyzed through an experimental procedure. In sequence, an experimental non-ideal system was built and instrumented, in this part, results were obtained for his behavior as well as the Sommerfeld effect was observed. After previously analysis, a controller that activates based on the system’s frequency was then implemented thought the coupling of the SMA actuator in the non-ideal structure. The Sommerfeld Effect and vibration amplitudes present in a non-ideal system as well as his attenuation using a smart material actuator are discussed. Detailed discussion is also made about the reduction of current consumption of the electric motor. The final results show that the coupling of the SMA material has a positive impact in reducing the amplitudes of vibration and the Sommerfeld effect, also presenting advantages such as the reduction of the electric current consumed and thus increasing the useful life of the system.